1985
DOI: 10.1210/endo-116-1-311
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation: A Mechanism for Ethanol-Associated Testicular Injury in Rats*

Abstract: Chronic alcohol administration leads to hepatic membrane alterations which, at least in part, are due to lipid peroxidation and may contribute to the toxicity of ethanol at the level of the hepatocyte. Because changes in testicular function also occur after chronic administration of ethanol to rats, we evaluated testicular mitochondria for evidence of alcohol-associated peroxidation injury which might contribute to the gonadal injury that occurs with prolonged use of the drug. Lipid peroxidation was assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 22 publications
2
29
1
Order By: Relevance
“…It is known that ethanol induces apoptotic cell death in testicular germ cells and suppresses spermatogenesis [14]. Previous our study demonstrated that ethanol significantly increased the number of apoptotic cells in both spermatogonia and spermatocytes [11].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It is known that ethanol induces apoptotic cell death in testicular germ cells and suppresses spermatogenesis [14]. Previous our study demonstrated that ethanol significantly increased the number of apoptotic cells in both spermatogonia and spermatocytes [11].…”
Section: Discussionsupporting
confidence: 50%
“…It is known to cause serious reproductive disorders, including testicular atrophy, accessory reproductive organ dysfunction, and infertility [1,5,6]. In particular, ethanol produces an oxidative stress within the testis and enhances apoptotic cell death [11,14,18].…”
mentioning
confidence: 99%
“…The mechanisms of this injury were previously studied. One is that ethanol metabolism produces an oxidative stress within the testes [15]; another is that ethanol exposure changes either testosterone [16] or esterone levels [17]. In addition, Zhu et al showed that ethanol exposure adversely affected the secretory function of Sertoli cells [18] and their recent research revealed enhanced apoptosis within the testes after chronic ethanol exposure [19].…”
Section: Introductionmentioning
confidence: 99%
“…These various findings have been interpreted as evidence that lipid peroxidation has occurred in the liver as a result of ethanol metabolism. Lipid peroxidation has also been proposed as a mechanism of ethanol-induced toxicity in the heart (10), gastric mucosa (11), and testes (12). However, the role of peroxidative events in the development of human alcoholrelated disease is highly controversial.…”
mentioning
confidence: 99%